Text Coherence and cohesion: language or pedagogical problem? - Alkhatib, Mohammed (Didáctica. Lengua y Literatura, 2012)
The objective of our research is to show the importance that we must attribute, learners and teachers, to the coherence (manifested in the overall level of text) and to the cohesion (manifested at the local level of text) to achieve a clear and understandable text. We showed the main points to be considered in the coherence and cohesion with illustrative examples. We concluded that cohesion is rather a linguistic knowledge (connectors, anaphora ...), and coherence requires pedagogical knowledge, such as the technique and mechanism to manage the structure of a text. Each teacher is expected to consider these two elements in the proofreading of learners by giving importance not only to the sentence, but also to the entire text.
Keywords: coherence; cohesion; teaching; learner; text; connector; anaphora.